Socially-labour problems of investment processes development in agriculture - Lanchenko, Ye. O. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The trends in investment and reproduction processes in agriculture are established, the state of employment in rural areas and the level of payment of labour in the agricultural sector are analyzed in the paper. Strategic directions of decision of socially-labour problems of economic development of agriculture are defined.